The importance of the smallest effect size of interest in expert witness testimony on alcohol and memory - Otgaar, Henry; Riesthuis, Paul; Ramaekers, Johannes G.; Garry, Maryanne; Kloft, Lilian (Frontiers in Psychology, 2022)
Memory experts are sometimes asked to evaluate the validity of accounts of witnesses, victims, or suspects. In some of these cases, they are asked what effect alcohol has on the validity of such accounts. In this article, we offer a guide on what expert witnesses can reliably say about how alcohol affects memory. We do so by resorting to effect sizes from previous studies and meta-analytic work, and address this novel question: are these effect sizes meaningful in legal cases? More specifically, we argue that any determination of whether individual studies about alcohol and memory are practically relevant for legal cases, scientists must focus on the smallest effect size of interest. We make the case that a decrease or increase of only 1 detail, especially an incorrect detail, should be regarded as the smallest effect size of interest in this line of research. In line with this idea, we show that effect sizes in the alcohol and memory literature are often larger than this smallest effect size of interest. This finding is important because it implies that alcohol often exerts a practically relevant and meaningful detrimental effect on the reporting of both correct and incorrect details, which in turn negatively affects the validity of witness testimony.